2022
DOI: 10.1186/s12866-022-02435-y
|View full text |Cite
|
Sign up to set email alerts
|

The global regulators ArcA and CytR collaboratively modulate Vibrio cholerae motility

Abstract: Background Vibrio cholerae, a Gram-negative bacterium, is highly motile owing to the presence of a single polar flagellum. The global anaerobiosis response regulator, ArcA regulates the expression of virulence factors and enhance biofilm formation in V. cholerae. However, the function of ArcA for the motility of V. cholerae is yet to be elucidated. CytR, which represses nucleoside uptake and catabolism, is known to play a chief role in V. cholerae pathogenesis and flagellar synthesis but the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…For example, over 1100 E. coli genes are regulated directly or indirectly by ArcA (Salmon et al, 2005). ArcA also acts as a global regulator in V. cholerae, affecting virulence, biofilm formation and motility (Li et al, 2022;Sengupta et al, 2003;Xi et al, 2020;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, over 1100 E. coli genes are regulated directly or indirectly by ArcA (Salmon et al, 2005). ArcA also acts as a global regulator in V. cholerae, affecting virulence, biofilm formation and motility (Li et al, 2022;Sengupta et al, 2003;Xi et al, 2020;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The arcA-knockout mutant exhibited a hypomotile phenotype under nutrient-poor conditions. Due to the derepression of rpoS transcription in the arcA-knockout mutant (see above) and previous experiments byLi et al (2022), showing an increase in the motility phenotype of the ΔarcA mutant, caused by the repression of flrA transcription by ArcA, a hypermotile phenotype was expected. FlrA is the master regulator of flagella biosynthesis and part of the Class I flagella transcription hierarchy.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Such loss of flagellar gene expression has been observed among diverse bacteria that are tightly packed in tissues (similar to the condition of the light organ at night, when V. fischeri symbionts are at high cell density) [ 95 ]. Flagellar gene expression is known to be repressed by several of the regulators of quorum-sensing and luminescence production (LitR represses flagellin genes, as does AinS [ 96 ]), as well as environmental stress response regulators (in V. cholera , ArcA represses flagellar gene expression and represses CytR (the negative regulator of competence, which is repressed by free environmental DNA and nucleosides) [ 97 ]). Somewhat surprisingly, symbiont transcriptome data has revealed that expression of flagellar structural genes is upregulated several hours before venting at dawn [ 85 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The procedures of the lux reporter assay were described in a previous study [ 84 ]. The amplification products of the respective promoter regions were digested and cloned into the XhoI-BamHI site, upstream of the lux genes, in the plasmid pMS402.…”
Section: Methodsmentioning
confidence: 99%